2009
DOI: 10.1142/s0218001409007466
|View full text |Cite
|
Sign up to set email alerts
|

Solution Over-Fit Control in Evolutionary Multiobjective Optimization of Pattern Classification Systems

Abstract: The optimization of many engineering systems is challenged by the solution over-fit to the data set used to evaluate potential solutions during the evolutionary process. The solution over-fit phenomenon is hard to detect and is especially prevalent in problems involving example-based training, such as pattern feature selection and pattern classifier design. For these applications, uncontrolled over-fit can lead to biased features being extracted and degraded classifier generalization abilities. This paper deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Several search algorithms have been applied in the literature for classifier selection, ranging from ranking the n best classifiers [19] to genetic algorithms (GAs) [28,33]. Ensemble combination performance [27], diversity measures [33,1,30] and ensemble size [23] are search criteria which are often employed. GAs are attractive since they allow the fairly easy implementation of classifier selection tasks as optimization processes [32].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several search algorithms have been applied in the literature for classifier selection, ranging from ranking the n best classifiers [19] to genetic algorithms (GAs) [28,33]. Ensemble combination performance [27], diversity measures [33,1,30] and ensemble size [23] are search criteria which are often employed. GAs are attractive since they allow the fairly easy implementation of classifier selection tasks as optimization processes [32].…”
Section: Introductionmentioning
confidence: 99%
“…Tsymbal et al [34] suggested that using individual member accuracy (instead of ensemble accuracy) together with diversity in a genetic search can overcome overfitting. Radtke et al [23] proposed a global validation method for multi-objective evolutionary optimization including classifier ensemble selection.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations